???/??, ??/??)-expansion method for analytical solutions of Jimbo-Miwa equation - Yokuş, Asıf; Durur, Hülya (My University, 2021)
The main goal of this study is obtaining analytical solutions for (3+1)-dimensional Jimbo- Miwa Equation which the second equation in the well-known KP hierarchy of integrable systems. For the (3+1DJM) equation, hyperbolic, trigonometric, complex trigonometric and rational traveling wave solutions have been constructed by applying the (???/??, 1/??)- expansion method. Then, real and imaginary graphics are presented by giving special values to the constants in the solutions obtained. These graphics are a special solution of the (3+1DJM) equation and represent a stationary wave of the equation. The (???/??, 1/??)- expansion method is an effective and powerful method for solving nonlinear evolution equations (NLEEs). Ready computer package program is used to obtain the solutions and graphics presented in this study.
Keywords: Matematik